Predictive Simulation of the Human Sit-to-Stand Transition - Korendiy, Vitaliy; Markovych, Bohdan; Tys, Mykhailo; Vyshnevskyi, Oleksandr (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
The sit-to-stand transition is a fundamental human movement, the performance of which serves as a critical biomarker for functional independence, particularly in aging and clinical populations. Difficulties in executing this mechanically demanding task are associated with decreased mobility, increased risk of institutionalization, and higher mortality rates. While experimental studies have provided foundational knowledge, computational simulation has emerged as an indispensable tool for non-invasively probing the internal biomechanics and neuromuscular control strategies governing this movement. Predictive simulations, in particular, offer the unique capability to establish causal relationships between neuromuscular deficits and functional impairments, and to design and evaluate interventions in silico.